1996
DOI: 10.1161/01.res.78.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epoxyeicosatrienoic Acids as Endothelium-Derived Hyperpolarizing Factors

Abstract: Endothelial cells release several compounds, including prostacyclin, NO, and endothelium-derived hyperpolarizing factor (EDHF), that mediate the vascular effects of vasoactive hormones. The identity of EDHF remains unknown. Since arachidonic acid causes endothelium-dependent relaxations of coronary arteries through its metabolism to epoxyeicosatrienoic acids (EETs) by cytochrome P450, we wondered if the EETs represent EDHFs. Precontracted bovine coronary arteries relaxed in an endothelium-dependent manner to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
1,074
7
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,105 publications
(1,130 citation statements)
references
References 30 publications
42
1,074
7
7
Order By: Relevance
“…It has also been reported that EETs, another candidate for EDHF, 31 stimulate the transient receptor potential vanilloid type 4 channels, which increases the calcium influx, and subsequently activates BKCa channels in rat smooth muscle cells. 32 Taken together, it is plausible to speculate that enhanced EDHF-like relaxation in the mesenteric arteries of DS rats fed a high-salt diet could be attributable to an enhanced EETs/ transient receptor potential vanilloid type 4/BKCa signaling pathway.…”
Section: Upregulation Of Edhf In Salt-induced Hypertension K Goto Et Almentioning
confidence: 97%
“…It has also been reported that EETs, another candidate for EDHF, 31 stimulate the transient receptor potential vanilloid type 4 channels, which increases the calcium influx, and subsequently activates BKCa channels in rat smooth muscle cells. 32 Taken together, it is plausible to speculate that enhanced EDHF-like relaxation in the mesenteric arteries of DS rats fed a high-salt diet could be attributable to an enhanced EETs/ transient receptor potential vanilloid type 4/BKCa signaling pathway.…”
Section: Upregulation Of Edhf In Salt-induced Hypertension K Goto Et Almentioning
confidence: 97%
“…For example, EETs activate Ca 2+ -sensitive K + channels (BK Ca ) in vascular smooth muscle cells resulting in hyperpolarization of the resting membrane potential and vasodilation of the coronary circulation [19][20][21]. This effect is diminished upon hydrolysis of EETs to DHETs by sEH [22].…”
Section: Arachidonic Acid Cyp Epoxygenases and Soluble Epoxide Hydromentioning
confidence: 99%
“…The phospholipase inhibitors mepacrine and dimethyl-eicosadienoic acid (DEDA) decrease relaxation to ACh but not AA, suggesting AA or a metabolite may be involved in the relaxations (11). AA is metabolized by COX, lipoxygenase (LO), and cytochrome P-450 pathways into bioactive eicosanoids (10,30,40,48). Using specific inhibitors in rabbit aorta, Singer and Peach (51) first concluded that a LO metabolite mediates the NO-and PG-resistant relaxation to ACh (51).…”
mentioning
confidence: 99%